Sex Differences in Outcome After Endovascular Stroke Therapy for Acute Ischemic Stroke. Issue 9 (September 2019) - Sheth, Sunil A.; Lee, Songmi; Warach, Steven J.; Gralla, Jan; Jahan, Reza; Goyal, Mayank; Nogueira, Raul G.; Zaidat, Osama O.; Pereira, Vitor M.; Siddiqui, Adnan; Lutsep, Helmi; Liebeskind, David S.; et al.
Abstract : Background and Purpose—: We determined the effect of sex on outcome after endovascular stroke thrombectomy in acute ischemic stroke, including lifelong disability outcomes. Methods—: We analyzed patients treated with the Solitaire stent retriever in the combined SWIFT (Solitaire FR With the Intention for Thrombectomy), STAR (Solitaire FR Thrombectomy for Acute Revascularization), and SWIFT PRIME (Solitaire FR With the Intention for Thrombectomy as Primary Endovascular Treatment) cohorts. Ordinal and logistic regression were used to examine known factors influencing outcome after endovascular stroke thrombectomy and study the effect of sex on the association between these factors and outcomes, including age and time to reperfusion. Years of optimal life after thrombectomy were defined as disability-adjusted life years and calculated by projecting disability through adjusted poststroke life expectancy by sex. Results—: Among 389 patients treated with endovascular stroke thrombectomy, 55% were females, and median National Institutes of Health Stroke Scale was 17 (interquartile range, 8–28). There were no differences between females versus males in presenting deficit severity (National Institutes of Health Stroke Scale score, 17 versus 17, P =0.21), occlusion location (69% versus 64% M1, P =0.62), presenting infarct extent (Alberta Stroke Program Early CT Score 8 versus 8, P =0.24), rate of substantial reperfusion (Thrombolysis in Cerebral Infarction 2b/3, 87% versus 83%, P =0.37), onset to reperfusion time (294 versus 302 minutes, P =0.46). Despite older ages (69 versus 64, P <0.001) and higher rate of atrial fibrillation (45% versus 30%, P =0.002) for females compared with males, adjusted rates of functional independence at 90 days were similar (odds ratio, 1.0; 95% CI, 0.6–1.6). After adjusting for age at presentation and stroke severity, females had more years of optimal life (disability-adjusted life year) after endovascular stroke thrombectomy, 10.6 versus 8.5 years ( P <0.001). Conclusions—: Despite greater age and higher rate of atrial fibrillation, females experienced comparable functional outcomes and greater years of optimal life after intervention compared with males. Abstract : Supplemental Digital Content is available in the text.